Investigation on natural blue colorant of clitoria ternatea l. fabaceae (bunga telang): the effects of stabilizers to extracts - Nurul Amira, Ahmad Yusof (2015)
Clitoria ternatea Linn Fabaceae which is also known as bunga telang in Malaysia, contains many useful functions leading to various activities such as blue food colorant, a cure for cancer and used for treatment from poisonous bite. Demand on the natural blue colorant is increasing due to the health issues from the usage of blue synthetics colorant. The study deals with the identification of phenolic compound in the extract which is anthocyanin by using High-performance Liquid Chromatography (HPLC) at wavelength of 520 nm and cyanidin-3-glucoside as a standard. The color stability of Clitoria ternatea flower is easy to be affected by several factors such as pH and temperature. For that reason, the color stability investigation was performed by combining the extract with two types of stabilizer which are Maltodextrin DE10 (MD) and Trehalose (T) with ratio 3:10 (w/v). The degradation of anthocyanin content at -different temperature was analysed by applying heat treatment on the samples using water bath shaker at 40°C, 60°C, and 80°C for 30 and 45 minutes. From HPLC results, anthocyanin was found at minutes of 2.01 according to retention time order. The total anthocyanin content (TAC) were analysed by using UV-vis spectrophotometer at two wavelengths which 510 nm and 700 nm in two different pH of buffer solution which are pH 1 and pH 4.5. The results showed that the value of TAC were same for extraction at 30 minutes time for all temperatures which 35.54 mgIL but the TAC of 60°C were dramatically decrease to 19.02 mg/L due to the sensitivity anthocyanin towards temperature above 50°C. In stabilizer addition analysis, the study was divided into four samples which are pure (1), MD (2), T (3) and, MID mixed with T (60:40) (4). The samples were tested for storage temperatures of 25°C and 4°C for four weeks. Initially, the TAC (mg/L) for both temperature were same which 80.08 (1), 75.41 (2), 46.88(3), and 106.28 (4). All of the samples for both of temperatures were showed degradation on week of 4. Results showed the TAC was degraded after 30 minutes on the heat treatment analysis. From all these findings, it is concluded that anthocyanin is an unstable compound which can easily be affected by temperature but by adding the stabilizers, there is a potential for blue food colorant application from Clitoria ternatea flowers to replace the current usage of blue synthetic colorant.